InSAR-based observations of the 2020-2021 transient deformation and the 2023 earthquake in Noto Peninsula, Japan - Yohei Kinoshita (Earth, Planets and Space)
Abstract The northeastern region of the Noto Peninsula experienced sudden seismic activity, accompanied by transient displacement since the end of 2020. During this period of heightened seismic activity, a magnitude 6.5 earthquake (Japan Meteorological Agency magnitude scale, $$M_{JMA}$$ M JMA ) occurred on May 5, 2023, within the region of active seismicity. Here, I performed a Sentinel-1 interferometric synthetic aperture radar (InSAR) time-series analysis to detect transient continuous displacement and investigate the mechanism of this event. The derived InSAR time series indicated an approximately 2 cm/year line-of-sight (LOS) change featuring an inflation pattern until the end of 2021. For the 2023 $$M_{JMA}$$ M JMA 6.5 earthquake, I performed InSAR analysis with ALOS-2 stripmap mode images and found that the coseismic displacement reached 20 cm in the LOS direction. Bayesian inversion for the transient continuous displacement suggested that the point source model showed the lowest root mean square error (RMSE) among the different source model types, the combination of a point source model and a rectangular reverse slip model showed a lower RMSE than single-source model cases. The estimated slip distribution for the 2023 earthquake revealed a maximum reverse-type slip of 177 cm at a depth of 7.8 km, which was the upper part of the seismically estimated hypocenter. The Coulomb failure stress change ( $$Δ $$ Δ CFS) on the 2023 earthquake fault was calculated based on the combined source model estimated from the Sentinel-1 time series. Overall, the $$Δ $$ Δ CFS showed positive values in zones where the depths were greater than 10 km, indicating that the 2023 earthquake fault may be affected to promote the earthquake triggering by the preceding activity since late 2020. Graphical Abstract